Legal Actions Arising in the Context of Genocide -A Study In Light of the Philosophy of Iraqi Civil Law- - Al-Jaafari, Osamah (Journal of Legal Sciences, 2026)
The will represents the essence of a legal act and the legal basis for its existence. In order for a legal act to be legitimate in producing its legal effects, it must emanate from a free, conscious, and enlightened will. Since genocide undermines this essence of a legal act and destroys the basis of its legal existence due to the collective fear it arouses, which nullifies freedom and will, the individual, under the shadow of genocide, becomes an unfree being seeking survival. His need for survival may drive him to conclude legal acts that are not based on free will, but rather on awe and fear. These legal acts thus lack their legal basis and essence, and thus lose their legitimacy and do not produce their effects. This necessitates the recovery of personal and property rights that have been transferred from one's responsibility to others under the weight of fear aroused by genocide.